(untitled) (The Research of Medical Science Review, 2024)
Introduction: Asthma is a prevalent chronic inflammatory disease of the airways which is characterized by sporadic airflow restriction and hyper-responsive bronchial tissue. Objective: To determine the frequency of parental smoking in children suffering from childhood asthma presenting at a tertiary care hospital. Methodology: This cross-sectional study was conducted at the Department of Pediatrics, University of Child Health Science, and the Children’s Hospital, Lahore. Data were collected through non-probability consecutive sampling was used to select participants for the study. Baseline characteristics, including age, gender, duration of asthma, and severity of asthma, were documented on a proforma. Results: A total of 100 children diagnosed with childhood asthma were included in the study with a mean age of 9.2 ± 3.4 years. Of the participants, 55% were male and 45% were female. Regarding asthma severity, 70% had mild asthma, 20% had moderate asthma, and 10% had severe asthma. Parental smoking was reported in 18% of cases, with 11% of parents smoking indoors and 7% smoking outdoors. The average number of cigarettes smoked per day was 12 ± 5, and the average duration of smoking was 10.3 ± 4.1 years. Conclusion: It is concluded that parental smoking is significantly associated with the frequency and severity of asthma symptoms in children. Exposure to secondhand smoke, particularly indoors, worsens asthma exacerbations, with higher levels of smoking correlating to more frequent symptoms.